2014
DOI: 10.3109/0886022x.2014.983017
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic protective effects of ceftriaxone and ascorbic acid against subacute deltamethrin-induced nephrotoxicity in rats

Abstract: Deltamethrin (DLM) is a synthetic class II pyrethroid acaricide and insecticide widely used for veterinary and agricultural purposes. However, its animal and human exposure leads to nephrotoxicity. Our experimental objective was to evaluate protective effects of ceftriaxone and/or ascorbic acid against DLM-induced renal injury in male Wistar albino rats. DLM-treated animals revealed significant alterations in serum biochemical parameters related to renal injury; urea, uric acid and creatinine. There was a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…Avidin‐horseradish peroxidase conjugate was used to oxidize 2,2′‐azino‐bis(3‐ethylbenzothiazoline‐6‐sulfonic destructive), which made a chromogen whose obsession was comparing to the centralization of the cytokine being assessed. The estimations were measured at a wavelength of 405 nm through spectrophotometry …”
Section: Methodsmentioning
confidence: 99%
“…Avidin‐horseradish peroxidase conjugate was used to oxidize 2,2′‐azino‐bis(3‐ethylbenzothiazoline‐6‐sulfonic destructive), which made a chromogen whose obsession was comparing to the centralization of the cytokine being assessed. The estimations were measured at a wavelength of 405 nm through spectrophotometry …”
Section: Methodsmentioning
confidence: 99%
“…In addition, further studies on the effects of “soluble” ceftriaxone on renal tubular cells would be of interest to better understand the pathophysiology of ceftriaxone-associated AKI. Note that the soluble ceftriaxone exhibited non-antimicrobial protective effects in models of neurological diseases, that is, Alexander’s disease [33, 34], Parkinson’s disease [35], and early brain injury after subarachnoid hemorrhage [36] and nephrotoxicity due to deltamethrin insecticide [37] and cadmium metal [38]. It is suspected that renal tubular cells would recognize and respond to soluble ceftriaxone and Cef-Ca crystals differently, and possession of this knowledge may have translational potentials in pediatric precision medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin C can also restore the antioxidant abilities of vitamin E, suggesting that one of its major functions is to recycle the tocopheroxyl radical (Mirvaghefi, Ali, & Poorbagher, ). Vitamin C ameliorated oxidative stress induced by various toxicants such as chlorpyrifos, deltamethrin and cisplatin (Abdel‐Daim et al, ; Abdel‐Daim & El‐Ghoneimy, ; Ambali, Onukak, et al, ). In addition, studies have showed the protective effect of vitamin C against DZN‐induced oxidative stress in fish blood (Mirvaghefi et al, ) and rat kidney (Abdel‐Daim, ) for 4 weeks and in rat brain after 24 hr (Yilmaz, Yilmaz, & Altuntas, ).…”
Section: Introductionmentioning
confidence: 99%